Analisis Model Pengelolaan Zakat, Infaq dan Shadaqah pada Lembaga Zakat Al-Washliyah (LAZWASHAL) - Muhammad Hafiz; Yenni Samri Juliati Nasution (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the management model of zakat, infaq, and shadaqah at the Al-Washliyah Zakat Institution (LAZWASHAL). Zakat, infak, and sadaqah are activities carried out by someone to fulfill their obligations and clean their assets. Indonesian people have enthusiasm in distributing zakat, infaq, and shadaqah. The research method used is qualitative with a descriptive approach. The technique of collecting research data through the subjects studied both from observation and interviews. The results showed that the LAZWASHAL zakat management model, namely productive zakat, is zakat that has a sustainable value and certainly does not run out. It has a target, namely the welfare of the community so that those who were recipients become zakat distributors or donors. in the form of providing business capital, providing donations in the form of groceries, cash to scholarships.